Immediate breast reconstruction following nipple-sparing mastectomy in an Asian population: Aesthetic outcomes and mitigating nipple-areolar complex necrosis - Wan-Sze Pek; Bien-Keem Tan; Yvonne Ying Ru Ng; Veronique Kiak Mien Tan; Mohamed Zulfikar Rasheed; Benita Kiat Tee Tan; Kong Wee Ong; Yee Siang Ong (Archives of Plastic Surgery, 2018)
Background Nipple-sparing mastectomies (NSMs) are increasingly performed to obtain the best aesthetic and psychological outcomes in breast cancer treatment. However, merely preserving the nipple-areolar complex (NAC) does not guarantee a good outcome. Darkly pigmented NACs and a tendency for poor scarring outcomes are particular challenges when treating Asian patients. Herein, we review the reconstructive outcomes following NSM at Singapore General Hospital.